ANALISIS TIPE KEPRIBADIAN PADA PESERTA DIDIK KELAS VII SEKOLAH MENENGAH PERTAMA NEGERI - Novandini, Desi; Yuline, Yuline; Fergina, Ana (Universitas Tanjungpura, 2023)
This study aims to determine the personality types of class VII students at SMP Negeri 7 Sungai Raya. Based on this problem, the researcher wants to describe introvert and extrovert personality types in class VII students of SMP Negeri 7 Sungai Raya. The research method used is descriptive method with a quantitative approach using a survey research form. The subjects or samples in this study were 36 respondents from a total population of 136 students in class VII A to VII E. The data collection technique used was an indirect communication technique with a data collection tool in the form of a questionnaire distributed via Google form. The data analysis used in this study is a percentage analysis technique. The results of data analysis in the study showed that: (1) Introverted personality traits had results with a percentage of 60% with indicators not good at getting along with a percentage of 67%, quiet with a percentage of 57%, hard to understand with a percentage of 61%, like to be alone with a percentage of 57 %, often afraid of other people with a percentage of 55% (2) Extrovert personality traits have results with a percentage of 67% with indicators sociable with a percentage of 66%, open with a percentage of 69%, friendly with a percentage of 66%, easy to adjust to percentage 67%. This study can be concluded in general that the personality type of class VII students at SMP Negeri 7 Sungai Raya has a percentage of 63% which is in the medium category.